Iatrogenic Obturator Hip Dislocation with Intrapelvic Migration - Shachar Kenan; Spencer Stein; Robert Trasolini; Daniel Kiridly; Bruce A. Seideman (Case Reports in Orthopedics)
Obturator hip dislocations are rare, typically resulting from high-energy trauma in native hips. These types of dislocations are treated with closed reduction under sedation. Open reduction and internal fixation may be performed in the presence of associated fractures. Still rarer are obturator hip dislocations that penetrate through the obturator foramen itself. These types of dislocations have only been reported three other times in the literature, all within native hips. To date, there have been no reports of foraminal obturator dislocations after total hip arthroplasty. We report of the first periprosthetic foraminal obturator hip dislocation, which was caused iatrogenically during attempts at closed reduction of a posterior hip dislocation in the setting of a chronic greater trochanter fracture. Altered joint biomechanics stemming from a weak hip abductor mechanism rendered the patient vulnerable to this specific dislocation subtype, which ultimately required open surgical intervention. An early assessment and identification of this dislocation prevented excessive closed reduction maneuvers, which otherwise could have had detrimental consequences including damage to vital intrapelvic structures. This case report raises awareness to this very rare, yet potential complication after total hip arthroplasty.